Autosomal dominant Parkinson's disease caused by SNCA duplications. (January 2016) - Konno, Takuya; Ross, Owen A.; Puschmann, Andreas; Dickson, Dennis W.; Wszolek, Zbigniew K.
Abstract: The discovery in 1997 that mutations in the SNCA gene cause Parkinson's disease (PD) greatly advanced our understanding of this illness. There are pathogenic missense mutations and multiplication mutations in SNCA . Thus, not only a mutant protein, but also an increased dose of wild-type protein can produce autosomal dominant parkinsonism. We review the literature on SNCA duplications and focus on pathologically-confirmed cases. We also report a newly-identified American family with SNCA duplication whose proband was autopsied. We found that over half of the reported cases with SNCA duplication had early-onset parkinsonism and non-motor features, such as dysautonomia, rapid eye movement sleep behavior disorder (RBD), hallucinations (usually visual) and cognitive deficits leading to dementia. Only a few cases have presented with typical features of PD. Our case presented with depression and RBD that preceded parkinsonism, and dysautonomia that led to an initial diagnosis of multiple system atrophy. Dementia and visual hallucinations followed. Our patient and the other reported cases with SNCA duplications had widespread cortical Lewy pathology. Neuronal loss in the hippocampal cornu ammonis 2/3 regions were seen in about half of the autopsied SNCA duplication cases. Similar pathology was also observed in SNCA missense mutation and triplication carriers.